Estrés y desempeño laboral en los colaboradores de una entidad financiera en Iquitos 2024 - Valera Catashunga, Greta Elizabeth (2025)
The purpose of this research was to determine how stress is related to the work performance of employees of a financial institution in Iquitos 2024, starting from the formulation of the problem that investigated the influence of various dimensions of stress (organisational climate, organisational structure, organisational territory, technology, influence of the leader, lack of cohesion and group support) on work productivity. A non-experimental, cross-sectional, basic design was used, applying structured questionnaires with Likert scales to a sample of 30 employees. Inferential analyses using chi-square tests revealed moderate and significant relationships between global stress and work performance, as well as between each of the dimensions assessed and employee performance. The results showed that the higher the level of stress in each dimension, the greater the impact on performance, which supports the importance of implementing stress management strategies and improvements in organisational processes. In conclusion, it was confirmed that stress and its dimensions are moderately related to job performance, suggesting the need for comprehensive interventions to optimise the work environment and productivity in the financial institution.